Degradation of 3-chlorocarbazole in water by sulfidated zero-valent iron/peroxymonosulfate system: Kinetics, influential factors, degradation products and pathways. (June 2022) - Sun, Zhuyu; Geng, Dan; Wu, Xiuling; Zhu, Luxiang; Wen, Jin; Wang, Le; Zhao, Xiaoxiang
Abstract: As an emerging class of organic contaminants, polyhalogenated carbazoles (PHCZs) have been increasingly detected all over the world since 1980s. Due to the environmental persistence, bioaccumulation, and dioxin-like toxicity, PHCZs have aroused widespread concerns in recent years. However, efficient approach for the degradation of PHCZs is quite limited so far. Therefore, in this study, an advanced oxidation process (AOP), sulfidated zero-valent iron/peroxymonosulfate (S-ZVI/PMS) system was used to degrade 3-chlorocarbazole (3-CCZ), which is one of the mostly detected PHCZs congeners. The degradation of 3-CCZ was systematically studied under different conditions by varying the molar ratio of S/Fe, the dosage of S-ZVI or PMS, pH and temperature. The results indicated that S-ZVI/PMS was an effective strategy for PHCZs treatment. The 20-min degradation efficiency of 3-CZZ was up to 96.6% with the pseudo-first-order rate constant of 0.168 min −1 under the conditions of 5 mg/L 3-CZZ, 0.3 g/L S-ZVI (S/Fe = 0.2), 1.0 mM PMS, pH 5.8 and 25 °C. HCO3 −, Cl − and humic acid (HA) showed inhibitory effects to different degrees. Results of the electron paramagnetic resonance (EPR) and scavenging experiments clarified the dominant role of OH, followed by 1 O2 and SO4 ─ . The product analysis and DFT calculation revealed three degradation pathways of 3-CCZ, namely hydroxylation, dechlorination and C–N bond cleavage, which largely alleviated the toxicity of the parent compound. This study showed the effectiveness of S-ZVI/PMS system in PHCZs treatment and provided a comprehensive investigation on the degradation behaviors of PHCZs in AOPs. Graphical abstract: Image 1 Highlights: S-ZVI/PMS system could effectively degrade 3-CCZ. OH was the dominant reactive species followed by 1 O2 and SO4 ─ . Hydroxylation, dechlorination and C–N bond cleavage were initial degradation pathways. The toxicities of the degradation products were greatly alleviated.